PENGGUNAAN KOAGULAN (TAWAS) DALAM PROSES PENJERNIHAN AIR DI LINGKUNGAN PADANGLOLO KELURAHAN KASSA KECAMATAN BATULAPPA KABUPATEN PINRANG - Ilham Syam; Nurhidayanti (Jurnal Pengabdian Masyarakat Gerakan Aksi Sehat (GESIT), 2018)
Water is the main element of life. In terms of quantity, water must meet all the needs and activities of daily living in accordance with the level of community life, because water is a source for life. And in terms of quality, water must meet the requirements of clean water quality according to Peraturan Menteri Kesehatan Republik Indonesia No. 416 / MENKES / IX / 1990 on terms of water quality in terms of physical, microbiological, chemical, and radioactive water. There are various simple ways that we can use to get clean water, one of the processes undertaken to reduce the turbidity of the water is by coagulation process, The process of coagulation is the process of collecting particles that can’t precipitated deposited turbidity by gravity, into particles larger so it can be precipitated by coagulant chemicals (alum). Alum serves to separate and precipitate impurities in water. The purpose of this activity is to give understanding to the residents in Padanglolo Environment about the importance of utilization of clean water that fulfill the requirements in accordance with the Peraturan Menteri Kesehatan Republik Indonesia No. 416 / MENKES / IX / 1990. From the data obtained that people in the environment Padanglolo for utilization of clean water facilities still have not reached the target, where the percentage that does not use clean water that is as much as 92% (323 people). After counseling and demonstration of coagulant (alum), the community has begun to understand and understand about the impacts caused by consuming water that does not meet health requirements.